Seasonal litter production patterns in three tropical forests in Sulawesi, Indonesia: Implications for managing secondary forests - PUTU SUPADMA PUTRA; AMRAN ACHMAD; TOSHIHIRO YAMADA; PUTU OKA NGAKAN (Society for Indonesian Biodiversity, 2023)
Abstract. Putra PS, Achmad A, Yamada T, Ngakan PO. 2023. Seasonal litter production patterns in three tropical forests in Sulawesi, Indonesia: Implications for managing secondary forests. Biodiversitas 24: 852-860. We studied the seasonal patterns of litter production in three tropical forests (Karst, Lowland, and Pine) on the Indonesian island of Sulawesi and measured environmental factors related to litter production from June 2019 to May 2020. Permanent plots of 0.4 ha to 1.0 ha were established in each forest to analyze forest structure and species composition. Thirty-six traps with a surface area of 1 m2 were installed to collect litterfall. The results showed the highest species diversity in the Karst forest, the highest tree density in the Lowland forest, and the largest basal area in the Pine forest. The most excellent litter production was in the Lowland forest (1,607.21 g/m2/year), followed by the Pine forest (1,288.24 g/m2/year) and Karst forest (1,099.83 g/m2/year). Litter production was more significant in the dry season in Karst and Pine forests, but there was no inter-seasonal difference in Lowland forest. Rainfall was the only environmental factor that differed between seasons. Differences in phenological adaptation between pioneer and climax species that comprise each forest likely account for the observed differences in litter production patterns.